Indicators for adequate diabetes care for the indigenous communities of Ecuador - Jimmy Martin‐Delgado; Carla Tovar; Israel Pazmiño; Amelia Briones; Irene Carrillo; Mercedes Guilabert; José Joaquín Mira (Wiley, 2022)
Abstract Introduction Diabetes is the second leading cause of death in Ecuador, as 79% of the indigenous population live in rural areas that are difficult to access and have below‐average health resources. The objective of this study was to define person‐centred indicators to monitor the care received by patients with diabetes in the indigenous population. Method Qualitative research combining three focus groups (with the participation of 10 patients and 18 professionals) to capture relevant information and Delphi to reach a consensus on the pertinence, relevance, and feasibility of a set of indicators was conducted. Two rounds of the Delphi technique were performed, with the participation of 64 professionals in the first round (90% response rate) and 34 in the second round (53% response rate). Results A total of 23 indicators were identified which were distributed in the previously identified six dimensions (cosmovision, accessibility, adaptability to cosmovision, resources, equipment, community care, quality culture and results). Conclusions The consensus on the set of indicators among all the participants in this study strengthened the results obtained. These indicators have considered the feasibility and relevance and aimed to achieve comprehensive person‐centred care for diabetes among the indigenous population in Ecuador and possibly the Andean community. Patient or Public Contribution These indicators' development included patients and caregivers since its conception. During the qualitative phase of this research, relevant information on cultural and social beliefs was gathered directly from the study population to achieve patient‐centred indicators for adequate diabetes care.